PENINGKATAN KEMANDIRIAN BELAJAR MELALUI BIMBINGAN KLASIKAL DI SMPN 2 BUKITTINGGI - Ayu Lestari; Syawaluddin; Rita Anggraini (CV. ADIBA AISHA AMIRA, 2023)
This research started from the fact that there were some students at SMPN 2 Bukittinggi in class 8.1 who were still looking at their friends when doing their assignments, then there were some students who submitted their assignments not on time, then there were some students who when working in groups did not participate enough in doing the group assignments, Then there are also some students who are late for class in the learning process, and there are some students who, when asked a question, are still confused about the answer and need the help of a friend next to their seat. Researchers try to apply classical guidance to increase students' learning independence. This research aims to reduce the lack of independence in students' learning. The method used in this research is pre-experiment, one group pre-test, post-test. The subjects in this research were students at SMPN 2 Bukittinggi class 8.1 who lacked learning independence based on observation results. The data analysis technique uses the Wilcoxon rank test. The instrument used in this research is a measurement scale in the form of a questionnaire. The results of the research can be seen from the implementation of the pre-test and post-test with an increase in each student. Analysis of the Wilcoxon signed rank test shows that the value of 0.000 is lower than 0.05, so it can be concluded that there is an increase in learning independence through classical guidance at SMPN 2 Bukittinggi.